High-water-resistance transparent composite EVA (Ethylene Vinyl Acetate) adhesive film suitable for TOPCon single glass
By using a three-layer composite transparent photovoltaic adhesive film in TOPCon battery modules, the problem of poor waterproofing and water blocking effects of battery modules is solved, and the effect of high water blocking and low water vapor transmission is achieved, extending the service life of the battery module and reducing costs.
Patent Information
- Application Number
- CN202411942197.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-11
AI Technical Summary
The waterproof and water-blocking effects of TOPCon battery components are not good, resulting in water vapor penetration affecting the power generation and service life of the battery cells.
A three-layer structure composite transparent photovoltaic adhesive film is adopted. The first and third layers are ethylene-vinyl acetate copolymer (EVA) layers, and the second layer is a mixture of ethylene and octene polymers and low-density polyethylene. It is prepared by a multi-layer coextrusion process to form a high water-resistance and low water vapor transmittance film.
It effectively reduces the water vapor transmission rate, prevents water vapor penetration, avoids corrosion of battery cells, extends the service life of battery components, and reduces production costs.
Smart Images

Figure BDA0005212780540000091 
Figure BDA0005212780540000092 
Figure BDA0005212780540000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photovoltaic adhesive films, and in particular to a high-water-resistance transparent composite EVA adhesive film suitable for TOPCon single glass. Background Art
[0002] In recent years, the application of solar cells has made amazing progress, and crystalline silicon cells have always occupied the vast majority of the world's total solar cell production due to their high photoelectric conversion efficiency and mature production technology. Crystalline silicon cells generally refer to crystalline silicon solar cells, which include monocrystalline silicon solar cells and polycrystalline silicon thin-film solar cells. TOPCon cells are a type of photovoltaic crystalline silicon cells. In recent years, due to their obvious advantages such as high conversion efficiency, low attenuation performance, and high mass production cost performance, they have been gradually adopted by industry companies. A TOPCon component is commonly used in the market now, which is composed of tempered glass, composite transparent photovoltaic film, battery cell, composite transparent photovoltaic film and tempered glass from top to bottom.
[0003] CN202411423636.7 discloses a three-layer composite EVA encapsulation film, comprising a first adhesive layer, a second adhesive layer and a third adhesive layer arranged in sequence; the first adhesive layer comprises the following components in weight: 85-95wt% of EVA resin, 5-15wt% of a first anti-PID agent, 0.6-1wt% of a second anti-PID agent and 1-5wt% of a first auxiliary agent; the first auxiliary agent comprises a cross-linked silane oligomer; the second adhesive layer comprises the following components in weight: 100wt% of EVA resin, 1-3wt% of a composite self-crosslinking agent, 0.1-0.5wt% of a water-binding agent and 0.5-4wt% of a second auxiliary agent; the third adhesive layer comprises the following components in weight: 85-95wt% of EVA resin, 5-15wt% of a composite acid-binding agent and 1-5wt% of a third auxiliary agent. This technology uses only EVA resin, which is prone to hydrolysis to produce more acid in contact with the battery cell, causing corrosion to the battery cell.
[0004] CN202311692619.9 discloses a composite adhesive film for photovoltaic module encapsulation, wherein the composite adhesive film is a three-layer structure, including a first pre-crosslinked adhesive film layer, a second uncrosslinked adhesive film layer and a third uncrosslinked adhesive film layer; the first pre-crosslinked adhesive film layer is an adhesive film layer that has been cured by ultraviolet light and heat; the first pre-crosslinked adhesive film layer is in direct contact with the battery of the photovoltaic module. The pre-crosslinking degree of this technology will fluctuate greatly, which is easy to cause instability and thus affect the power of the module.
[0005] CN202222792767.5 discloses a single-glass TOPCon battery assembly, comprising glass, a first adhesive film, a TOPCon battery array, a second adhesive film and a backplane arranged in sequence, wherein the second adhesive film comprises a water-absorbing layer having water-absorbing properties. This technology uses POE as the main water-blocking layer, which has worse water-blocking properties than LDPE and is more expensive.
[0006] Therefore, in order to solve the above technical problems, the present invention proposes a composite transparent photovoltaic adhesive film with low cost and low water vapor transmission rate. Summary of the invention
[0007] In order to solve the technical problems of poor waterproof and water-blocking effects of TOPCon battery modules and aging of battery modules, the composite transparent photovoltaic adhesive film with good water-blocking performance obtained by the present invention effectively reduces the water vapor permeability, thereby improving the penetration of water vapor on the side of the solar battery module, avoiding the corrosion of the battery sheet, thereby affecting the power generation and service life of the battery sheet.
[0008] The present invention provides a composite transparent photovoltaic adhesive film for making TOPCon battery components. Since the high polymers of ethylene and octene are expensive, using low-density polyethylene instead of the high polymers of ethylene and octene can reduce the cost while having a strong water-blocking effect.
[0009] In order to solve the above technical problems, the present invention first provides a TOPCon battery encapsulation water-blocking film, which has three layers from the position of the battery cell to the outside, the first layer is ethylene-vinyl acetate copolymer (EVA layer), the second layer is a mixture of ethylene and octene polymer and low-density polyethylene, and the third layer is ethylene-vinyl acetate copolymer (EVA layer); the second layer of the mixture of ethylene and octene polymer and low-density polyethylene includes mode (1) or mode (2),
[0010] Mode (1), the raw materials of the mixture of the second layer include 50-90wt% of low-density polyethylene a (LDPE resin particles), 6-46.6wt% of ethylene and octene polymer (POE), 0.1-1wt% of organic peroxide, 0.1-2wt% of auxiliary cross-linking agent, 0.1-0.5wt% of silane coupling agent, and 0.1-0.5wt% of light stabilizer;
[0011] Mode (2), the raw materials of the mixture of the second layer include 20-80wt% of low-density polyethylene a (LDPE resin particles), 10-30wt% of low-density polyethylene b (LDPE resin particles), 6-46.6wt% of ethylene and octene polymers (POE resin), 0.1-1wt% of organic peroxide, 0.1-2wt% of co-crosslinking agent, 0.1-0.5wt% of silane coupling agent, and 0.1-0.5wt% of light stabilizer, the low-density polyethylene a has a melt index of 5-45g / 10min and a melting point of 50-100°C; the low-density polyethylene b has a melt index of 5-10g / 10min and a melting point of 50-100°C.
[0012] Among them, the high polymer of ethylene and octene mixed with low-density polyethylene plays a strong water-blocking role. And because low-density polyethylene is cheaper than the high polymer of ethylene and octene, the composite transparent photovoltaic adhesive film of the present invention has a good water-blocking effect and can reduce costs.
[0013] Preferably, the raw materials of the ethylene-vinyl acetate copolymer (EVA layer) (first layer and third layer) include 96.5-99.7wt% of ethylene-vinyl acetate copolymer (EVA resin particles), 0.1-1wt% of organic peroxide, 0.05-1wt% of co-crosslinking agent, 0.1-0.5wt% of silane coupling agent, 0.02-0.5wt% of antioxidant, and 0.03-0.5wt% of light stabilizer.
[0014] Preferably, the ethylene-vinyl acetate copolymer (EVA resin particles) has a melt index of 3-30 g / 10 min and a melting point of 60-100°C.
[0015] Preferably, the content of the ethylene-vinyl acetate copolymer (EVA resin particles) is 97.0wt%, 97.5w%, 98.0w%, 98.5w%, 99.0w%, or 99.5w%.
[0016] Preferably, the organic peroxide content of the ethylene-vinyl acetate copolymer (EVA layer) is 0.2wt%, 0.5wt%, or 0.8wt%.
[0017] Preferably, the organic peroxide of the ethylene-vinyl acetate copolymer (EVA layer) includes tert-butyl peroxy isopropyl carbonate, 1,3-1,4-di(tert-butyl peroxy isopropyl) benzene, benzoyl peroxide, diisopropyl peroxide, 2,5-dimethyl 2,5-bis(tert-butyl peroxy) hexane, tert-butyl peroxy isopropyl carbonate, 1,1-bis(tert-butyl peroxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-amyl peroxy) Any one or a combination of at least two of -3,3,5-trimethylcyclohexane, 1,1-bis(tert-amylperoxy)cyclohexane, 2,2-bis(tert-butylperoxy)butane, tert-amyl peroxycarbonate, tert-butyl peroxy-3,3,5-trimethylhexanoate, tert-butyl peroxycarbonate-2-ethylhexyl ester, tert-butyl peroxy-2-ethylhexyl carbonate, tert-butyl peroxyformate-2-ethylhexyl ester and tert-butyl peroxycarbonate-2-ethylhexyl ester. The organic peroxide is easily decomposed by light or heat to generate free radicals, which can trigger a crosslinking reaction.
[0018] Preferably, the content of the cross-linking agent in the ethylene-vinyl acetate copolymer (EVA layer) is 0.1wt%, 0.2wt%, 0.5wt%, 0.7wt% or 0.9wt%.
[0019] Preferably, the auxiliary crosslinking agent of the ethylene-vinyl acetate copolymer (EVA layer) includes one or more of glycidyl methacrylate, methyl methacrylate, trimethylolpropane trimethacrylate, propoxylated glycerol triacrylate, 2-carboxyethyl acrylate, 2-hydroxyethyl methacrylate phosphate, triallyl isocyanurate, triisopropyl isocyanurate, trimethylolpropane triacrylate, pentaerythritol triacrylate and ethoxylated trimethylolpropane triacrylate. The auxiliary crosslinking agent can be used as a vulcanizing agent for photovoltaic encapsulation film and improve training efficiency.
[0020] Preferably, the content of the silane coupling agent in the ethylene-vinyl acetate copolymer (EVA layer) is 0.2wt%, 0.3wt% or 0.4wt%.
[0021] Preferably, the silane coupling agent of the ethylene-vinyl acetate copolymer (EVA layer) includes one or more of vinyl trimethoxy silane, vinyl triethoxy silane, vinyl triethoxy silane, acrylate phosphate, vinyl tri(β-methoxyethoxy) silane, vinyl triisopropoxy silane, γ-(methacryloxypropyl) trimethoxy silane and aminoethylaminopropyl trimethoxy silane. The silane coupling agent is used to improve adhesion and dispersibility.
[0022] Preferably, the antioxidant content of the ethylene-vinyl acetate copolymer (EVA layer) is 0.05wt%, 0.1wt%, 0.2wt%, 0.3wt%, or 0.4wt%.
[0023] Preferably, the antioxidant of the ethylene-vinyl acetate copolymer (EVA layer) can be one or more of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester, N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl) hexanediamine, 4,4'-thiobis(6-tert-butyl-3-methylphenol), tris[2,4-di-tert-butylphenyl]phosphite and 3,3'-thiobispropionate (octadecyl) ester. The antioxidant can improve the antioxidant performance and extend the service life.
[0024] Preferably, the content of the light stabilizer in the ethylene-vinyl acetate copolymer (EVA layer) is 0.05wt%, 0.1wt%, 0.2wt%, 0.3wt% or 0.4wt%.
[0025] Preferably, the light stabilizer of the ethylene-vinyl acetate copolymer (EVA layer) includes one or more of bis-2,2,6,6-tetramethylpiperidinol sebacate, phenyl o-hydroxybenzoate, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-n-octyloxybenzophenone, 2-(2'-hydroxy-3',5'-di-tert-phenyl)-5-chlorobenzotriazole, monobenzoic acid resorcinol ester and hexamethylphosphoric triamide. The light stabilizer can be used in combination with an antioxidant to improve heat resistance, and can be used in combination with an ultraviolet absorber to further improve the light stabilization effect.
[0026] Preferably, the low-density polyethylene a has a melt index of 5-45 g / 10 min and a melting point of 50-100° C., and the low-density polyethylene b has a melt index of 5-10 g / 10 min and a melting point of 50-100° C. The two are mixed to adjust the melt index to be more in line with the processing parameters of conventional EPE films, so as to reduce the appearance and performance problems of the film caused by the difference in fluidity during processing.
[0027] Preferably, in the embodiment (1), the content of the low-density polyethylene a (LDPE resin particles) is 60wt%, 70wt%, 80wt% or 85wt%.
[0028] Preferably, in the method (1), the polymer of ethylene and octene has a melt index of 5-40 g / 10 min and a melting point of 50-100°C.
[0029] Preferably, in the embodiment (1), the content of the polymer of ethylene and octene is 10wt%, 15wt%, 20wt%, 30wt% or 40wt%.
[0030] Preferably, in the embodiment (1), the content of the organic peroxide is 0.2 wt%, 0.5 wt%, or 0.8 wt%.
[0031] Preferably, in the method (1), the organic peroxide includes tert-butyl peroxy isopropyl carbonate, 1,3-1,4-di(tert-butyl peroxy isopropyl) benzene, benzoyl peroxide, diisopropyl peroxide, 2,5-dimethyl 2,5-bis(tert-butyl peroxy) hexane, tert-butyl peroxy isopropyl carbonate, 1,1-bis(tert-butyl peroxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-amyl peroxy)-3,3, Any one or a combination of at least two of 5-trimethylcyclohexane, 1,1-bis(tert-amylperoxy)cyclohexane, 2,2-bis(tert-butylperoxy)butane, tert-amyl peroxycarbonate, tert-butyl peroxy-3,3,5-trimethylhexanoate, tert-butyl peroxycarbonate-2-ethylhexyl ester, tert-butyl peroxy-2-ethylhexyl carbonate, tert-butyl peroxyformate-2-ethylhexyl ester and tert-butyl peroxycarbonate-2-ethylhexyl ester. The organic peroxide is easily decomposed by light or heat to generate free radicals, which can trigger a crosslinking reaction.
[0032] Preferably, in the method (1), the content of the auxiliary cross-linking agent is 0.15wt%, 0.2wt%, 0.5wt%, 0.7wt%, 0.9wt% or 1.5wt%.
[0033] Preferably, in the method (1), the auxiliary crosslinking agent includes one or more of glycidyl methacrylate, methyl methacrylate, trimethylolpropane trimethacrylate, propoxylated glycerol triacrylate, 2-carboxyethyl acrylate, 2-hydroxyethyl methacrylate phosphate, triallyl isocyanurate, triisopropyl isocyanurate, trimethylolpropane triacrylate, pentaerythritol triacrylate and ethoxylated trimethylolpropane triacrylate. The auxiliary crosslinking agent can be used as a vulcanizing agent for photovoltaic encapsulation film and improve training efficiency.
[0034] Preferably, in the embodiment (1), the content of the silane coupling agent is 0.2wt%, 0.3wt% or 0.4wt%.
[0035] Preferably, in the method (1), the silane coupling agent includes one or more of vinyl trimethoxy silane, vinyl triethoxy silane, vinyl triethoxy silane, acrylate phosphate, vinyl tri(β-methoxyethoxy) silane, vinyl triisopropoxy silane, γ-(methacryloxypropyl) trimethoxy silane and aminoethylaminopropyl trimethoxy silane. The silane coupling agent is used to improve adhesion and dispersibility.
[0036] Preferably, in the embodiment (1), the content of the light stabilizer is 0.2wt%, 0.3wt% or 0.4wt%.
[0037] Preferably, in the method (1), the light stabilizer includes one or more of bis-2,2,6,6-tetramethylpiperidinol sebacate, phenyl o-hydroxybenzoate, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-n-octyloxybenzophenone, 2-(2'-hydroxy-3',5'-di-tert-phenyl)-5-chlorobenzotriazole, monobenzoic acid resorcinol ester and hexamethylphosphoric triamide. The light stabilizer can be used in combination with an antioxidant to improve heat resistance, and can be used in combination with an ultraviolet absorber to further improve the light stabilization effect.
[0038] Preferably, in the method (2), the content of the low-density polyethylene a (LDPE resin particles) is 30wt%, 40wt%, 50wt%, 60wt% or 70wt%.
[0039] Preferably, in the embodiment (2), the content of the low-density polyethylene b (LDPE resin particles) is 15wt%, 20wt%, or 25wt%.
[0040] Preferably, in the embodiment (2), the content of the polymer of ethylene and octene (POE resin) is 10wt%, 15wt%, 20wt%, 25wt%, 35wt% or 40wt%.
[0041] Preferably, in the embodiment (2), the content of the organic peroxide is 0.2 wt%, 0.5 wt%, or 0.8 wt%.
[0042] Preferably, in the method (2), the organic peroxide includes tert-butyl peroxy isopropyl carbonate, 1,3-1,4-di(tert-butyl peroxy isopropyl) benzene, benzoyl peroxide, diisopropyl peroxide, 2,5-dimethyl 2,5-bis(tert-butyl peroxy) hexane, tert-butyl peroxy isopropyl carbonate, 1,1-bis(tert-butyl peroxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-amyl peroxy)-3,3, Any one or a combination of at least two of 5-trimethylcyclohexane, 1,1-bis(tert-amylperoxy)cyclohexane, 2,2-bis(tert-butylperoxy)butane, tert-amyl peroxycarbonate, tert-butyl peroxy-3,3,5-trimethylhexanoate, tert-butyl peroxycarbonate-2-ethylhexyl ester, tert-butyl peroxy-2-ethylhexyl carbonate, tert-butyl peroxyformate-2-ethylhexyl ester and tert-butyl peroxycarbonate-2-ethylhexyl ester. The organic peroxide is easily decomposed by light or heat to generate free radicals, which can trigger a crosslinking reaction.
[0043] Preferably, in the method (2), the content of the auxiliary cross-linking agent is 0.15wt%, 0.2wt%, 0.5wt%, 0.7wt%, 0.9wt% or 1.5wt%.
[0044] Preferably, in the method (2), the auxiliary crosslinking agent includes one or more of glycidyl methacrylate, methyl methacrylate, trimethylolpropane trimethacrylate, propoxylated glycerol triacrylate, 2-carboxyethyl acrylate, 2-hydroxyethyl methacrylate phosphate, triallyl isocyanurate, triisopropyl isocyanurate, trimethylolpropane triacrylate, pentaerythritol triacrylate and ethoxylated trimethylolpropane triacrylate. The auxiliary crosslinking agent can be used as a vulcanizing agent for photovoltaic encapsulation film and improve training efficiency.
[0045] Preferably, in the embodiment (2), the content of the silane coupling agent is 0.2wt%, 0.3wt% or 0.4wt%.
[0046] Preferably, in the method (2), the silane coupling agent includes one or more of vinyl trimethoxy silane, vinyl triethoxy silane, vinyl triethoxy silane, acrylate phosphate, vinyl tri(β-methoxyethoxy) silane, vinyl triisopropoxy silane, γ-(methacryloxypropyl) trimethoxy silane and aminoethylaminopropyl trimethoxy silane. The silane coupling agent is used to improve adhesion and dispersibility.
[0047] Preferably, in the embodiment (1), the content of the light stabilizer is 0.2wt%, 0.3wt% or 0.4wt%.
[0048] Preferably, in the method (1), the light stabilizer includes one or more of bis-2,2,6,6-tetramethylpiperidinol sebacate, phenyl o-hydroxybenzoate, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-n-octyloxybenzophenone, 2-(2'-hydroxy-3',5'-di-tert-phenyl)-5-chlorobenzotriazole, monobenzoic acid resorcinol ester and hexamethylphosphoric triamide. The light stabilizer can be used in combination with an antioxidant to improve heat resistance, and can be used in combination with an ultraviolet absorber to further improve the light stabilization effect.
[0049] Preferably, the thickness of the water-blocking film is 300-600 μm, or 350 μm, 400 μm, 450 μm, 500 μm, or 650 μm.
[0050] Preferably, the thickness ratio of the EVA layer, the POE mixed LDPE layer and the EVA layer is 1:(0.6-1.5):1, or 1:(0.7-1.2):1, 1:(0.8-1.1):1, 1:(0.9-1.0):1, 1:(0.92-0.96):1, 1:0.95:1.
[0051] Preferably, the thickness of the POE+LDPE layer is in the range of 50-200 μm, or 80 μm, 100 μm, 120 μm, or 140 μm.
[0052] Preferably, the water-blocking film is prepared by a multi-layer co-extrusion process.
[0053] The present invention also provides a method for preparing a TOPCon battery encapsulation water-blocking film, which adopts a multi-layer co-extrusion process and comprises:
[0054] Step (1), raw material mixing: uniformly mixing the EVA layer raw material and the second layer raw material respectively;
[0055] Step (2), cast co-extrusion: the EVA layer raw material is divided into two flow channels to form the first layer and the third layer, and the second layer raw material is one flow channel to form the second layer, and a transparent high water-resistant polyolefin encapsulation film for solar cells is prepared through plasticizing, extrusion, casting, pulling and winding.
[0056] Preferably, in the multi-layer co-extrusion casting, the extrusion section temperature of the first and third adhesive layers is 65-80°C, or 70°C or 75°C.
[0057] Preferably, in the multi-layer co-extrusion casting, the extrusion section temperature of the second adhesive layer is 70-80°C, or 72°C, 74°C, or 76°C, and the die head temperature is 80-85°C, or 82°C, 84°C.
[0058] Preferably, in the three-layer composite transparent adhesive film of the present invention, the POE+LDPE layer located between the two EVA layers has a strong water-barrier effect.
[0059] Preferably, the composite transparent photovoltaic film has a thickness of 300 to 600 μm, wherein the thickness range of the POE+LDPE layer is 50-200 μm; and the thickness ratio of the EVA layer, the POE mixed LDPE layer and the EVA layer is 1:(0.6 to 1.5):1.
[0060] By adopting the above technical solution, the total thickness of the water-blocking film is within the above range, the thickness is moderate, the water-blocking effect and other properties are good, and it can meet the application in this field. In addition, when the thickness ratio of the three-layer structure of the water-blocking film is within the above range, the water-blocking performance and other properties of the final water-blocking film are better.
[0061] The present invention also provides an application of a mixture of a high polymer of ethylene and octene and low-density polyethylene in a TOPCon battery encapsulation water-blocking adhesive film, which effectively reduces the water vapor transmission rate.
[0062] Preferably, for method (1), the water vapor permeability of the water-blocking film is no higher than 10.5 g / ㎡·d, or 10 g / ㎡·d, or 9.9 g / ㎡·d.
[0063] Preferably, for method (2), the water vapor permeability of the water-blocking film is no higher than 8 g / ㎡·d, or 7 g / ㎡·d, or 6 / ㎡·d.
[0064] Compared with the prior art, the product provided by the present invention has the following advantages or functions:
[0065] (1) The highly water-resistant three-layer composite transparent adhesive film of the present invention can effectively reduce the water vapor permeability, thereby improving the penetration of water vapor to the side of the solar cell double-glass module, avoiding the corrosion of the cell sheet, and effectively extending the service life of the TOPCon cell module.
[0066] (2) The water-blocking three-layer composite transparent adhesive film provided by the present invention uses LDPE which has a lower water vapor permeability than POE, and the price of LDPE is even lower. Therefore, the composite transparent photovoltaic adhesive film of the present invention has a better water-blocking effect and can reduce costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0067] Figure 1 It is a schematic diagram of a bar graph of water vapor transmission rate of the composite transparent photovoltaic film of Example 1;
[0068] Figure 2 This is the yellowing diagram of the composite transparent photovoltaic film PCT in Example 1 after aging;
[0069] Figure 3 This is the aging peeling diagram of the composite transparent photovoltaic film PCT of Example 1;
[0070] Figure 4 This is a schematic diagram of the structure of the composite transparent adhesive film of Example 1. DETAILED DESCRIPTION
[0071] A three-layer composite transparent adhesive film, the adhesive film consists of a core layer and two skin layers located above and below the core layer;
[0072] In order to make it easier to understand the structure of the present invention and the functional features and advantages that can be achieved, the preferred embodiments of the present invention are described in detail with reference to the drawings as follows:
[0073] The information of the raw materials involved in the specific implementation of the present invention is as follows:
[0074] EVA resin particles were obtained from Formosa Plastics Corporation, model 7760S, with a melt index of 25.32 g / 10 min and a melting point of 68.2°C.
[0075] LDPE resin particles a were obtained from Dushanzi Petrochemical, with model UL1488, melt index of 14.06 g / 10 min, and melting point of 64.5°C; LDPE resin particles b were obtained from Dushanzi Petrochemical, with model UL0588, melt index of 5.46 g / 10 min, and melting point of 65.7°C.
[0076] POE resin particle a is grafted with silane from 20070s, with a melt index of 14.46 g / 10 min and a melting point of 46.2 °C; POE resin particle b is from Dow PV8669 in the United States, with a melt index of 14.14 g / 10 min and a melting point of 76.1 °C; POE resin particle c is from Dow PV8660 in the United States, with a melt index of 4.86 g / 10 min and a melting point of 72.2 °C
[0077] Performance testing:
[0078] The water-blocking films obtained in the following examples and comparative examples were used to prepare a single-glass TOPCon battery module, which, from bottom to top, are backplane, water-blocking films obtained in the examples and comparative examples, battery cell, conventional EPE film, and glass panel. The obtained single-glass TOPCon battery module was tested.
[0079] Example 1
[0080] A three-layer composite transparent adhesive film with good water-blocking performance comprises the following ingredients: 97.70wt% of ethylene-vinyl acetate copolymer (EVA resin particles) as an EVA layer raw material, 0.62wt% of tert-butyl peroxy-2-ethylhexyl carbonate as a crosslinking agent, 0.41wt% of triallyl isocyanurate as an auxiliary crosslinking agent, 0.98wt% of trimethylolpropane trimethacrylate as an auxiliary crosslinking agent, 0.14wt% of silane coupling agent γ-(methacryloxypropyl) trimethoxysilane, 0.05wt% of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol, and 0.10wt% of light stabilizer diisocyanate. -2,2,6,6-tetramethylpiperidinol ester, the raw materials of the POE layer are 83.25wt% of low-density polyethylene a (LDPE resin particles), 16.69wt% of ethylene and octene polymers (POE), 0.29wt% of tert-amyl peroxycarbonate, 0.49wt% of tert-butyl peroxy-2-ethylhexyl carbonate, 0.49wt% of cross-linking agent triallyl isocyanurate, 0.49wt% of cross-linking agent trimethylolpropane trimethacrylate, 0.15wt% of silane coupling agent γ-(methacryloxypropyl) trimethoxysilane, and 0.15wt% of light stabilizer sebacic acid bis-2,2,6,6-tetramethylpiperidinol ester. The above components are mixed evenly in a mixing kettle, put into a casting machine and set the parameters, and after plasticization, extrusion, casting, traction, and winding, a transparent high-water-resistance polyolefin encapsulation film for solar cells is made. In multi-layer co-extrusion casting, the extrusion section temperature of the first and third adhesive layers is 65-80°C; the extrusion section temperature of the second adhesive layer is 70-80°C, and the die temperature is 80-85°C. The EVA reactor on the casting line has two flow channels, which can separate the EVA to form the first and third layers, and the POE reactor has only one flow channel, which forms the second layer. In two of the schemes, the layer thickness of the POE layer is 100μm and 150μm respectively.
[0081] Example 2
[0082] A three-layer composite transparent adhesive film with good water-blocking performance comprises the following ingredients: 97.70wt% of ethylene-vinyl acetate copolymer (EVA resin particles) as an EVA layer raw material, 0.62wt% of tert-butyl peroxy-2-ethylhexyl carbonate as a crosslinking agent, 0.41wt% of triallyl isocyanurate as an auxiliary crosslinking agent, 0.98wt% of trimethylolpropane trimethacrylate as an auxiliary crosslinking agent, 0.14wt% of silane coupling agent γ-(methacryloxypropyl)trimethoxysilane, 0.05wt% of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid] pentaerythritol ester as an antioxidant, and 0.10wt% of bis-2,2,6,6-tetramethylpiperidinium sebacate as a light stabilizer. The raw materials of the POE layer are 67.58wt% of low-density polyethylene a (LDPE resin particles), 15.67wt% of low-density polyethylene b (LDPE resin particles), 16.69wt% of ethylene and octene polymer a (POE), 0.29wt% of tert-amyl peroxycarbonate, 0.49wt% of tert-butyl peroxy-2-ethylhexyl carbonate, 0.49wt% of cross-linking agent triallyl isocyanurate, 0.49wt% of cross-linking agent trimethylolpropane trimethacrylate, 0.15wt% of silane coupling agent γ-(methacryloxypropyl) trimethoxysilane, and 0.15wt% of light stabilizer sebacic acid bis-2,2,6,6-tetramethylpiperidinol ester. The above components are mixed evenly in a mixing kettle, put into a casting machine and set the parameters, and are made into a transparent high-water-resistant polyolefin encapsulation film for solar cells through plasticization extrusion, casting, traction, and winding. In multi-layer co-extrusion casting, the extrusion section temperature of the first and third adhesive layers is 65-80°C; the extrusion section temperature of the second adhesive layer is 70-80°C, and the die temperature is 80-85°C. The EVA reactor on the casting line has two flow channels, which can separate the EVA to form the first and third layers, and the POE reactor has only one flow channel, which forms the second layer. In two of the schemes, the layer thickness of the POE layer is 100μm and 150μm respectively.
[0083] In addition, in other embodiments, when preparing the mixed raw material for the POE layer, low-density polyethylene, high polymers of ethylene and octene and other additives can be directly blended to obtain the mixed raw material; low-density polyethylene, high polymers of ethylene and octene and other additives can also be extruded and granulated, and then the obtained masterbatch can be directly involved in plasticization, extrusion and casting. Therefore, the above preparation method should not be a limitation on the technical solution and specific implementation methods of this application.
[0084] Example 3
[0085] A three-layer composite transparent adhesive film with good water-blocking performance comprises the following ingredients: 97.70wt% of ethylene-vinyl acetate copolymer (EVA resin particles) as an EVA layer raw material, 0.62wt% of tert-butyl peroxy-2-ethylhexyl carbonate as a crosslinking agent, 0.41wt% of triallyl isocyanurate as an auxiliary crosslinking agent, 0.98wt% of trimethylolpropane trimethacrylate as an auxiliary crosslinking agent, 0.14wt% of silane coupling agent γ-(methacryloxypropyl)trimethoxysilane, 0.05wt% of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid] pentaerythritol ester as an antioxidant, and 0.10wt% of light stabilizer di-2,2,6,6 sebacate. -tetramethyl piperidine alcohol ester, the raw material of the POE layer is 83.25wt% of low-density polyethylene a (LDPE resin particles), 16.69wt% of ethylene and octene polymer (POE), 0.29wt% of tert-amyl peroxycarbonate, 0.49wt% of tert-butyl peroxy-2-ethylhexyl carbonate, 0.49wt% of cross-linking agent triallyl isocyanurate, 0.49wt% of cross-linking agent trimethylolpropane trimethacrylate, 0.15wt% of silane coupling agent γ-(methacryloxypropyl) trimethoxysilane, 0.15wt% of light stabilizer sebacic acid bis-2,2,6,6-tetramethyl piperidine alcohol ester, and the particles are granulated by a granulator. The above components are mixed evenly in a mixing kettle, put into a casting machine and set the parameters, and after plasticization, extrusion, casting, traction, and winding, a transparent high-water-resistance polyolefin encapsulation film for solar cells is made. In multi-layer co-extrusion casting, the extrusion section temperature of the first and third adhesive layers is 65-80°C; the extrusion section temperature of the second adhesive layer is 70-80°C, and the die temperature is 80-85°C. The EVA reactor on the casting line has two flow channels, which can separate the EVA to form the first and third layers, and the POE reactor has only one flow channel, which forms the second layer. In two of the schemes, the layer thickness of the POE layer is 100μm and 150μm respectively.
[0086] Example 4
[0087] A three-layer composite transparent adhesive film with good water-blocking performance comprises the following ingredients: 97.70wt% of ethylene-vinyl acetate copolymer (EVA resin particles) as an EVA layer raw material, 0.62wt% of tert-butyl peroxy-2-ethylhexyl carbonate as a crosslinking agent, 0.41wt% of triallyl isocyanurate as an auxiliary crosslinking agent, 0.98wt% of trimethylolpropane trimethacrylate as an auxiliary crosslinking agent, 0.14wt% of silane coupling agent γ-(methacryloxypropyl) trimethoxysilane, 0.05wt% of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester as an antioxidant, 0.10wt% of sebacic acid bis-2,2,6,6-tetramethylpiperidinol ester as a light stabilizer, and POE layer The raw materials are 67.58wt% of low-density polyethylene a (LDPE resin particles), 15.67wt% of low-density polyethylene b (LDPE resin particles), 16.69wt% of ethylene and octene polymer (POE), 0.29wt% of tert-amyl peroxycarbonate, 0.49wt% of tert-butyl peroxy-2-ethylhexyl carbonate, 0.49wt% of auxiliary cross-linking agent triallyl isocyanurate, 0.49wt% of auxiliary cross-linking agent trimethylolpropane trimethacrylate, 0.15wt% of silane coupling agent γ-(methacryloxypropyl) trimethoxysilane, and 0.15wt% of light stabilizer bis-2,2,6,6-tetramethylpiperidinol sebacate, and the mixture is granulated by a granulator. The above components are mixed evenly in a mixing kettle, put into a casting machine and set the parameters. After plasticizing, extruding, casting, pulling and winding, a transparent and highly water-resistant polyolefin encapsulation film for solar cells is made. In the multi-layer co-extrusion casting, the extrusion section temperature of the first and third adhesive layers is 65-80°C; the extrusion section temperature of the second adhesive layer is 70-80°C, and the die head temperature is 80-85°C. The EVA kettle on the casting line has two flow channels, which can separate the EVA to form the first and third layers, and the POE kettle has only one flow channel, which constitutes the second layer. In two of the schemes, the layer thickness of the POE layer is 100μm and 150μm respectively.
[0088] Comparative Example 1
[0089] A three-layer composite transparent adhesive film comprises the following components in parts by weight: 97.70wt% of ethylene-vinyl acetate copolymer (EVA resin particles) as a raw material of an EVA layer, 0.62wt% of a cross-linking agent tert-butyl peroxy-2-ethylhexyl carbonate, 0.41wt% of an auxiliary cross-linking agent triallyl isocyanurate, 0.98wt% of an auxiliary cross-linking agent trimethylolpropane trimethacrylate, 0.14wt% of a silane coupling agent γ-(methacryloxypropyl) trimethoxysilane, 0.05wt% of an antioxidant tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol, and 0.10wt% of a light stabilizer di-2,2-dihydro-1,4-diol-1-sebacate. ,6,6-tetramethylpiperidinol ester, the raw materials of the POE layer are 69wt% of ethylene and octene polymer b (POE), 16wt% of ethylene and octene polymer c (POE), 15wt% of anti-PID masterbatch, 0.29wt% of tert-amyl peroxycarbonate, 0.49wt% of tert-butyl peroxy-2-ethylhexyl carbonate, 0.49wt% of auxiliary crosslinking agent triallyl isocyanurate, 0.49wt% of auxiliary crosslinking agent trimethylolpropane trimethacrylate, 0.15wt% of silane coupling agent γ-(methacryloxypropyl) trimethoxysilane, and 0.15wt% of light stabilizer sebacate bis-2,2,6,6-tetramethylpiperidinol ester. The above components are mixed evenly in a mixing kettle, put into a casting machine and set the parameters, and after plasticization, extrusion, casting, traction, and winding, a transparent and highly water-resistant polyolefin encapsulation film for solar cells is made. In multi-layer co-extrusion casting, the extrusion section temperature of the first and third adhesive layers is 65-80°C; the extrusion section temperature of the second adhesive layer is 70-80°C, and the die temperature is 80-85°C. The EVA reactor on the casting line has two flow channels, which can separate the EVA to form the first and third layers, and the POE reactor has only one flow channel, which forms the second layer. In two of the schemes, the layer thickness of the POE layer is 100μm and 150μm respectively.
[0090] Test 1—Water Vapor Transmission Rate Test
[0091] The water vapor transmission rate of the composite transparent adhesive film with good water barrier performance obtained in Examples 1-4 was tested. The specific test method and test results are as follows:
[0092] Test instrument: Water vapor transmission rate tester
[0093] Test principle: Fix the sample in the middle of the test chamber, and divide the test chamber into two chambers, the gas with stable relative humidity flows in the upper chamber of the film, and the dry gas flows in the lower chamber of the film. Water molecules diffuse through the sample into the dry gas on the other side and are carried to the sensor by the flowing gas. The water vapor concentration measured by the sensor is analyzed to calculate the water vapor transmission rate.
[0094] Technical parameters: temperature is 25℃, humidity of dry air in the lower chamber is 0%, humidity of gas in the upper chamber is 80%, and sample thickness is 0.4-0.6mm.
[0095] Table 1 Water vapor transmission rate test results of the composite transparent adhesive film of the embodiment and the comparative example
[0096]
[0097] From the test results of the above embodiments and comparative examples, it can be concluded that the water barrier performance of the comparative example meets the index, but is not excellent. The composite transparent adhesive film provided by the present invention has better water barrier performance than the conventional EPE adhesive film. For mode (1), the water vapor permeability of the water barrier film is not higher than 10.5 g / ㎡·d, and for mode (2), the water vapor permeability of the water barrier film is not higher than 8 g / ㎡·d.
[0098] Test 2—PCT Aging Test
[0099] The composite transparent adhesive film with good water-blocking performance obtained in Examples 1-4 was subjected to PCT aging test. The specific test method and test results are as follows:
[0100] Test standard: High temperature and high humidity aging performance test is carried out according to the experimental method of GB / T 34179-2017;
[0101] Damp heat aging: temperature 121°C, saturated humidity, take out after 48 hours;
[0102] Table 2 Aging test results of the composite transparent adhesive films of the embodiments and comparative examples
[0103]
[0104]
[0105] From the test results of the above embodiments and comparative examples, it can be concluded that the high temperature and high humidity resistance of the comparative example meets the index, but is not excellent. The composite transparent adhesive film provided by the present invention has better high temperature and high humidity resistance than the conventional EPE adhesive film. For mode (1), the PCT peeling force of the water-blocking adhesive film is higher than 60N / cm, and for mode (2), the PCT peeling force of the water-blocking adhesive film is higher than 60N / cm.
[0106] The above is only a preferred embodiment of the present invention and is not intended to limit the protection scope of the present invention. All equivalent changes and modifications made according to the content of the present invention are included in the patent scope of the present invention.
Claims
1. A TOPCon battery encapsulation water-blocking film, which has three layers from the position of the battery cell, the first layer is ethylene-vinyl acetate copolymer (EVA layer), the second layer is a mixture of ethylene and octene polymer and low-density polyethylene, and the third layer is ethylene-vinyl acetate copolymer (EVA layer); the second layer of the mixture of ethylene and octene polymer and low-density polyethylene includes method (1) or method (2), Mode (1), the raw materials of the mixture of the second layer include 50-90wt% of low-density polyethylene a (LDPE resin particles), 6-46.6wt% of ethylene and octene polymer (POE), 0.1-1wt% of organic peroxide, 0.1-2wt% of auxiliary cross-linking agent, 0.1-0.5wt% of silane coupling agent, and 0.1-0.5wt% of light stabilizer; Mode (2), the raw materials of the mixture of the second layer include 20-80wt% of low-density polyethylene a (LDPE resin particles), 10-30wt% of low-density polyethylene b (LDPE resin particles), 6-46.6wt% of ethylene and octene polymers (POE resin), 0.1-1wt% of organic peroxide, 0.1-2wt% of co-crosslinking agent, 0.1-0.5wt% of silane coupling agent, and 0.1-0.5wt% of light stabilizer, the low-density polyethylene a has a melt index of 5-45g / 10min and a melting point of 50-100°C; the low-density polyethylene b has a melt index of 5-10g / 10min and a melting point of 50-100°C.
2. The water-blocking film according to claim 1, characterized in that: The raw materials of the ethylene-vinyl acetate copolymer (EVA layer) include 96.5-99.7wt% of ethylene-vinyl acetate copolymer (EVA resin particles), 0.1-1wt% of organic peroxide, 0.05-1wt% of co-crosslinking agent, 0.1-0.5wt% of silane coupling agent, 0.02-0.5wt% of antioxidant and 0.03-0.5wt% of light stabilizer.
3. The water-blocking film according to claim 2, characterized in that: The ethylene-vinyl acetate copolymer (EVA resin particles) has a melt index of 3-30 g / 10 min and a melting point of 60-100° C.
4. The water-blocking film according to claim 1 or 2, characterized in that: The organic peroxide includes any one or a combination of at least two of tert-butyl peroxyisopropyl carbonate, 1,3-1,4-di(tert-butylperoxyisopropyl)benzene, benzoyl peroxide, diisopropyl benzene peroxide, 2,5-dimethyl 2,5-bis(tert-butylperoxy)hexane, tert-butyl peroxyisopropyl carbonate, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-amylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-amylperoxy)cyclohexane, 2,2-bis(tert-butylperoxy)butane, tert-amyl peroxycarbonate, tert-butyl peroxy-3,3,5-trimethylhexanoate, tert-butyl peroxycarbonate-2-ethylhexyl ester, tert-butyl peroxy-2-ethylhexyl carbonate, tert-butyl peroxyformic acid-2-ethylhexyl ester and tert-butyl peroxycarbonate-2-ethylhexyl ester.
5. The water-blocking film according to claim 1 or 2, characterized in that: The auxiliary cross-linking agent includes one or more of glycidyl methacrylate, methyl methacrylate, trimethylolpropane trimethacrylate, propoxylated glycerol triacrylate, 2-carboxyethyl acrylate, 2-hydroxyethyl methacrylate phosphate, triallyl isocyanurate, triisopropyl isocyanurate, trimethylolpropane triacrylate, pentaerythritol triacrylate and ethoxylated trimethylolpropane triacrylate.
6. The water-blocking adhesive film according to claim 1 or 2, characterized in that: The silane coupling agent includes one or more of vinyl trimethoxy silane, vinyl triethoxy silane, vinyl triethoxy silane, acrylate phosphate, vinyl tri(β-methoxyethoxy) silane, vinyl triisopropoxy silane, γ-(methacryloxypropyl) trimethoxy silane and aminoethylaminopropyl trimethoxy silane.
7. The water-blocking adhesive film according to claim 1 or 2, characterized in that: The antioxidant may be one or more of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine, 4,4'-thiobis(6-tert-butyl-3-methylphenol), tris[2,4-di-tert-butylphenyl]phosphite and di(octadecyl)thiodipropionate.
8. The water-blocking film according to claim 1 or 2, characterized in that: The light stabilizer includes one or more of bis-2,2,6,6-tetramethylpiperidinol sebacate, phenyl o-hydroxybenzoate, 2-(2′-hydroxy-5′-methylphenyl)benzotriazole, 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-n-octyloxybenzophenone, 2-(2′-hydroxy-3′,5′-di-tert-phenyl)-5-chlorobenzotriazole, monobenzoic acid resorcinol ester and hexamethylphosphoric triamide.
9. The water-blocking adhesive film according to claim 1 or 2, characterized in that: The high polymer of ethylene and octene has a melting index of 5-40 g / 10 min and a melting point of 50-100° C.
10. The water-blocking adhesive film according to claim 1 or 2, characterized in that: The thickness of the water-blocking film is 300-600 μm.
11. The water-blocking adhesive film according to claim 1 or 2, characterized in that: The thickness ratio of the EVA layer, the POE mixed LDPE layer and the EVA layer is 1:(0.6-1.5):
1.
12. A method for preparing a water-blocking film according to any one of claims 1 to 11, using a multi-layer co-extrusion process, comprising: Step (1), raw material mixing: uniformly mixing the EVA layer raw material and the second layer raw material respectively; Step (2), cast co-extrusion: the EVA layer raw material is divided into two flow channels to form the first layer and the third layer, and the second layer raw material is one flow channel to form the second layer, and a transparent high water-resistant polyolefin encapsulation film for solar cells is prepared through plasticizing, extrusion, casting, pulling and winding.
13. The preparation method according to claim 12, characterized in that: In the multi-layer co-extrusion casting, the extrusion section temperature of the first and third adhesive layers is 65-80°C.
14. The preparation method according to claim 12, characterized in that: In multi-layer co-extrusion casting, the extrusion section temperature of the second adhesive layer is 70-80°C.
15. The preparation method according to claim 12, characterized in that: In multi-layer co-extrusion casting, the die head temperature of the second adhesive layer is 80-85°C.
16. Use of the mixture of the high polymer of ethylene and octene and low-density polyethylene in any one of claims 1 to 11 in a TOPCon battery encapsulation water-blocking film to effectively reduce water vapor transmission rate.
17. The use according to claim 16, wherein for method (1), the water vapor permeability of the water-blocking film is not higher than 10.5 g / ㎡·d.
18. The use according to claim 16, wherein for method (2), the water vapor transmission rate of the water-blocking film is not higher than 8 g / ㎡·d.
Citation Information
Patent Citations
Composite adhesive film for packaging photovoltaic module as well as preparation method and application of composite adhesive film
CN117683476A
Three-layer composite EVA packaging adhesive film, preparation method thereof and photovoltaic module
CN119081573A
Single-glass TOPCon battery assembly
CN219066830U
Cited By
Composite adhesive film, N-type TOPCon photovoltaic module and photovoltaic equipment
CN224001332U